Proceedings of the International Conference on Industrial Engineering and Operations Management 2022
DOI: 10.46254/eu05.20220378
|View full text |Cite
|
Sign up to set email alerts
|

Supply Chain Resiliency in the Pharmaceutical Industry – a Simulation-Based Approach

Abstract: The recent COVID-19 pandemic has highlighted the key role of the pharmaceutical industry and its supply chain operations in society. Like in many other sectors, this pandemic has unveiled important vulnerabilities and weaknesses across the pharmaceutical distribution network, calling the attention for the importance of resiliency, flexibility, and sustainability strategies.One of the key challenges regarding resiliency is the ability to understand and anticipate the supply chain behaviour under uncertainty and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The simulation model was developed as an extension of the authors' previous work [11], using the AnyLogic software as shown in the conceptual framework presented in Figure 3.…”
Section: Simulation Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…The simulation model was developed as an extension of the authors' previous work [11], using the AnyLogic software as shown in the conceptual framework presented in Figure 3.…”
Section: Simulation Modelmentioning
confidence: 99%
“…Following the authors' previous work [11], a simulation-based approach is proposed here considering the integration of Agent-Based Simulation (ABS) and Discrete-Event-Simulation (DES) techniques, for the design and planning of the pharmaceutical supply chain. The proposed methodology allows an assessment of the impacts of resilience-driven strategies on the SC's overall performance to be made, and can be used to guide the decisionmaking process toward trade-off solutions, leading to waste reduction and increased access to medicines in low-income regions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations